CAPACITY STRENGTHENING PROGRAM FOR SMALL AND MEDIUM ENTERPRISES (SMES) IN RELIGIOUS TOURISM VILLAGE OF BONGO AT GORONTALO REGENCY - Ismet Sulila (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
Abstract The program on regional leading product development (program pengembangan produk unggulan daerah, henceforth called as PPPUD) for Karawo- the local Gorontalo’s embroidery product- has been carried out to domestic crafters in the Religious Tourism Village of Bongo from 2017 and expected to be completed by 2019. The initial year project focuses on strengthening the business management of the karawo, including strengthening the capacity of human resources and related production facilities. This capacity strengthening program is carried out in collaboration with the Cooperative, Industry, Trade and SMEs Department of Gorontalo regency. This initial year program has brought positive results that are evident in each of the following indicator: 1) the increase of managerial technical capacity of the management and all members of the SMEs groups, 2) all aspects of human resources are fulfilled and strengthened and thus, have brought impact on the quantity and the quality of the product; 3) all production-related facilities are fulfilled, and the office spaces are also furnished hence, have brought positive impact on production and the management activity, these improvement have brought impact on the marketing of the karawo products produced by these SMEs. Based on this initial year’s achievements, the focus of the second year would be on strengthening the production, finance, and raw material’s aspects of the karawo. Therefore, it is crucial for this community empowerment program through the PPUD program to be carried out into the next year.  Keywords: Management, Human Resource, Karawo Production Facilities and Products.